Impact properties of uniaxially thermoformed auxetic foams. (May 2022) - Zhang, Qicheng; Scarpa, Fabrizio; Barton, David; Zhu, Yunpeng; Lang, Zi-Qiang; Zhang, Dayi; Peng, Hua-Xin
Highlights: New class of uniaxially thermoformed auxetic foam under quasi-static and impact tests. Custom drop tower design described. Strain fields, poisson's ratios and energy absorption metrics in different planes measured. Parametric energy absorption metrics determined for different manufacturing parameters. Nagy's model to relate quasi-static stiffness to the dynamic one of these foams developed. Abstract: This work describes large strain quasi-static and impact tests of a new class of low-cost, uniaxially thermoformed, transverse isotropic auxetic foams with compression ratio ranging from 20 to 80%. A custom drop tower rig with high-speed cameras suitable for these soft porous foam materials is designed and used to perform impact tests with energy ranging from 0.38 to 1.90 J, corresponding to strain rates from 64/s to 143/s. The thermoformed foams only show auxeticity when loaded along the transverse direction to the uniaxial thermoforming compression, with Poisson's ratio V 21 reaching as low as −1.5 at 20% strain and then close to 0 at large strains. The samples deform with large shear band deformations, also due to the auxeticity. The negative Poisson's ratio foams along that transverse direction also show enhanced impact energy absorption performance, with normalized peak force reduction as high as ∼40% against the pristine foam; the reduction is however 20% along the thermoforming direction. A constitutive model based on Nagy's approach is applied to describe the enhancement of dynamic stress during the impact tests compared with the quasi-static one, due to strain rate effects.